Dynamic modeling and prediction of wax deposition thickness in crude oil pipelines - Martins Obaseki; Paul T. Elijah (Journal of King Saud University: Engineering Sciences)
This paper investigates wax deposition as one of the major problems encountered in oil and gas pipelines with a potential environmental damage and with huge financial implications. A molecular diffusion and aging mechanism model by Fick’s law is applied here to better predict wax deposition thickness in crude oil pipelines. Through theoretical derivation and numerical simulation, the diffusion rate into the deposit gel has been modified by modifying the deposit layer temperature to accommodate effect of flow velocity. Findings show that the wax deposit is not uniformly distributed along the pipe length. Data were analyzed based on impact changing oil inlet temperature, volumetric flow rate, and high viscosity using MATLAB software/Simulator. On validation series model convergence was found to perform better with reasonable agreement when compared with experimental data. The result of prediction can be used to determine other parameters in the pipe line such as effective diameter, actual pressure drop and volumetric flow rate in through the pipe.